A is for Australian reefs - Lessac, Frané (Candlewick Press, 2023)
"Along the Australian coastline, underwater reefs are bustling with the most amazing sea creatures living on the planet! What can blow bubble rings and swim through them? What has teeth on its eyeballs? What creature makes itself nearly invisible to predators by using camouflage? What poops out sand? Discover the answer to these questions plus many more incredible facts in this fascinating undersea exploration of Australian reefs."--